SPLINE-FUNCTIONS IN THE TASK OF THE FLOW AIRFOIL PROFILE - Lopatjuk, Mikhail (Proceedings of National Aviation University (archive), 2014)
The method and the algorithm of solving the problem of streamlining are presented. Neumann boundary problem is reduced to the solution of integral equations with given boundary conditions using the cubic spline-functions